A review of defect mitigation strategies for UMG-Si wafers - Basnet, Rabin; Macdonald, Daniel (Frontiers in Photonics, 2024)
This review focuses on the challenges and potential pathways for utilizing upgraded metallurgical-grade silicon (UMG-Si) in the silicon photovoltaic industry. UMG-Si is an attractive low-cost alternative silicon feedstock, but its bulk quality is compromised due to the presence of defects and impurities. The review begins by identifying and discussing the various defects and impurities commonly found in UMG-Si wafers, drawing insights from a literature survey. The detrimental effects of these defects on solar cell performance are highlighted. Next, the review provides a summary of defect mitigation strategies that have been employed to improve the bulk quality of UMG-Si wafers. These strategies include tabula rasa, impurity gettering, and defect/impurity passivation through hydrogenation. The effectiveness of these strategies is evaluated by considering carrier lifetimes and comparing them with those of conventional silicon wafers. The review then examines the reported open-circuit voltages and efficiencies of solar cells based on UMG-Si wafers. A comparison is made between the performance of UMG-Si solar cells and those fabricated on conventional silicon. The impact of defect mitigation strategies on the performance of UMG-Si solar cells is discussed, emphasizing the improvements achieved through these strategies.